(Hetero)anilines from dinitrogen via nucleophilic aromatic substitution at tungsten nitrido complexes - Eberle, Lukas; Ballmann, Joachim (Journal of the American Chemical Society, 2025)
A protocol for the arylation of both N atoms in dinitrogen is presented. This protocol relies on the use of tungsten pincer complexes to split N2 and generate tungsten nitrides, which were shown to undergo nucleophilic aromatic substitution (SNAr) reactions with electron-deficient aryl chlorides. Starting from (15N)2, this two-step process was exploited for the preparation of different 15N-labeled aryl amines.